Literature Review: Faktor Penyebab Stunting di Indonesia - Hidayati, Nur; Luvi Dian Afriyani; Iswardani, Ratih; Muskhofah Oviyanti; Ulfiana, Alfa; Sulpiana; Lallo, Polina; Sani, Nur Qhomaril Andrea; Handayani, Dwi; Murwanti; Muchtar, Warni (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2025)
Stunting is a condition of chronic malnutrition in children over an extended period, resulting in impaired growth, marked by a height that is shorter than the average for their age (Fitriani et al., 2022). UNICEF reported that in 2022, approximately 148.1 million children under five experienced stunting (UNICEF et al., 2023).  This research aimed to identify the factors that affect the prevalence of stunting in toddlers.  This research is based on a review of the literature derived from five articles selected in accordance with the research objectives. The literature was sourced from databases including Google Scholar, PubMed, Journal Center, and Sinta, covering the period from 2020 to 2025. The terms employed are factors and stunting. The literature study concludes that the determinants of stunting incidence in toddlers include nutritional status, dietary intake, nutritional status during pregnancy, family income, and environmental sanitation. Recommendations for Public Health Center to educate mothers of toddlers regarding appropriate nutrition, to regularly supply supplementary food for toddlers, to inform families about their crucial role, to disseminate knowledge on the significance of maintaining good environmental sanitation for children's optimal growth and development, and to consistently monitor children's nutritional status to prevent stunting.   Abstrak Stunting ialah kekurangan nutrisi pada anak dalam jangka waktu lama sehingga pertumbuhan anak menjadi terhambat yang ditandai dengan tinggi badan yang lebih rendah dibandingkan usianya (Fitriani et al. 2022). UNICEF mencatat di tahun 2022 sebanyak 148,1 juta balita mengalami stunting (UNICEF et ai., 2023). Penelitian ini  dilakukan untuk mengetahui faktor-faktor yang mempengaruhi terjadinya stunting pada balita. Penelitian ini di review dari literatur yang telah di identifikasi dari 5 artikel yang telah diseleksi sesuai dengan tujuan penelitian, adapun literatur yang direview melalui database yang digunakan  dalam pencarian artikel adalah google scholar, Pubmed, journal center,  dan sinta antara tahun 2020-2025.  Kata kunci yang digunakan yaitu faktor-faktor dan stunting. Kesimpulan dari literatur yang di teliti bahwa faktor yang mempengaruhi kejadian stunting pada balita adalah status gizi, pola makan, status gizi saat hamil, pendapatan keluarga dan sanitasi lingkungan. Saran bagi Puskesmas agar meberikan edukasi ataupun pemahaman kepada para ibu yang memiliki balita tentang pola makan yang benar, memberikan makanan tambahan bagi balita secara rutin, memberikan edukasi pentingnya peran keluarga, memberikan informasi lebih lanjut tentang sanitasi lingkungan yang baik terhadap lingkungan anak-anak agar tumbuh dan kembang anak lebih optimal sesuai usia,  rutin memantau status gizi anak agar anak tercegah dari kejadian stunting.